2020
DOI: 10.1002/arch.21685
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of apoptosis is an effective target gene for RNAi‐mediated control of Colorado potato beetle,Leptinotarsa decemlineata

Abstract: The Colorado potato beetle (CPB; Leptinotarsa decemlineata) is one of the most notorious and difficult to control pests of potato and other solanaceous crops in North America. This insect has evolved a remarkable ability to detoxify both plant and synthetic toxins, allowing it to feed on solanaceous plants containing toxic alkaloids and to develop resistance to synthetic chemicals used for its control. RNA interference (RNAi) is a natural mechanism that evolved as an immune response to double‐stranded RNA (dsR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Notably, the authors observed over 60% mortality after 3 days of feeding on dsRNA targeting actin (see Supplementary Material in Xu et al, 2021). These studies with P. versicolora, together with that of Máximo et al (2020), who observed effective L. decemlineata mortality after 2 days, suggest that RNAi can work in a timely manner in some coleopterans, perhaps in particular chrysomelids of the subfamily Chrysomelinae. Furthermore, studies performed in chrysomelids collectively suggest high dietary RNAi efficacy via various sources of dsRNA consumption (e.g., RNAi cultivar., naked dsRNA, and bacterially expressed dsRNA).…”
Section: Observed Rnai Sensitivities In Coleoptera Family Chrysomelidaementioning
confidence: 84%
“…Notably, the authors observed over 60% mortality after 3 days of feeding on dsRNA targeting actin (see Supplementary Material in Xu et al, 2021). These studies with P. versicolora, together with that of Máximo et al (2020), who observed effective L. decemlineata mortality after 2 days, suggest that RNAi can work in a timely manner in some coleopterans, perhaps in particular chrysomelids of the subfamily Chrysomelinae. Furthermore, studies performed in chrysomelids collectively suggest high dietary RNAi efficacy via various sources of dsRNA consumption (e.g., RNAi cultivar., naked dsRNA, and bacterially expressed dsRNA).…”
Section: Observed Rnai Sensitivities In Coleoptera Family Chrysomelidaementioning
confidence: 84%
“…Colorado potato beetle has strong RNAi response to environmental RNA as demonstrated by dsRNA targeting different genes under different experimental conditions in the laboratory and field ( Máximo et al, 2020 ; Mehlhorn et al, 2020 ; Petek et al, 2020 ). In our studies, we show consumption of leaf material treated with Ledprona caused larval death over time ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using dsRNA molecules to target insect essential genes have proven the susceptibility of CPB to RNAi and demonstrated the potential of this technology to control this pest ( Zhu et al, 2011 ; San Miguel and Scott, 2016 ; Máximo et al, 2020 ; Mehlhorn et al, 2020 ; Petek et al, 2020 ; Doğan et al, 2021 ). However, one of the key known limitations of this approach was the capacity to scale dsRNA production at a low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Host-induced gene silencing-mediated control of insect pests has been proven effective with an average of 50% conferred resistance (Koch and Wassenegger, 2021). Exogenous dsRNA and siRNA applications (e.g., feeding, injection, and oral delivery) to various insect pests and mites is routinely conducted to study gene function or identify RNAi targets (Lü et al, 2020;Mehlhorn et al, 2020Mehlhorn et al, , 2021Máximo et al, 2020). In line with the above discussion about RNAs that remain on sprayed surfaces and those that enter plant cells, insect pests and mites can ingest dsRNA and siRNAs by chewing-biting or piercing-sucking feeding behaviors.…”
Section: Significant Advances Of Rna Spray Controlling: Insectsmentioning
confidence: 99%
“…For these purposes, encapsulation is pursued to guarantee and prolong the longevity of RNA sprays in the field. For example, E. coli is not only utilized for cost-effective dsRNA production but also represents a protective envelope for efficient dsRNA delivery (Lü et al, 2020;Máximo et al, 2020;Wang et al, 2021;Wu et al, 2021). Interestingly, encapsulation of dsRNA, if large enough, may prevent cellular uptake (plant intake) and thus shield dsRNA from plant DCL processing, as indicated by previous breakthroughs demonstrating that the expression of dsRNA in chloroplasts (DCL-free organelles) targeting the ßactin gene of L. decemlineata (Colorado potato beetle) caused larval lethality (Zhang et al, 2015).…”
Section: Significant Advances Of Rna Spray Controlling: Insectsmentioning
confidence: 99%